PERANCANGAN SISTEM ADMINISTRASI PERSEDIAAN OBAT PADA APOTIK KOPEL - Indah Puspitorini; Triningsih Triningsih; Herudini Subariyanti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
In the era of information that is all advanced now, the need for fast information in its presentation is absolutely necessary to exist. To get the information quickly and precisely, one form of solution is to use a computerized information system. In the routine purchase and sale of goods, a systematic recording of goods inventory is needed. To avoid the overbalance and the lack of drug supplies, a good system of management should be used. As for the problems that are often faced in the administration of inventory at dispensaries that are still manual are the time needed to record the number of drugs entered and the number of drugs sold, there are deficiencies in recording returns of drugs that have been purchased or medicines sent from suppliers not according to order, so it is necessary to make a list of returns and a list of drugs that have been sold as a whole. The goal to be achieved from the design of this system is to design a drug inventory information system for comparison of the current manual system or can be a proposed system to be used so that it is useful to facilitate its service in achieving good goals.